Stimulants & hallucinogens - Monroe, Judy.; Kantar, Maythee (Mankato, MN, U.S.A. : Crestwood House, 1988)
Describes the origins, and uses of, and laws against such stimulants and hallucinogens as marijuana, cocaine, and crack.
Includes index.
1 13
Keywords: Children -- United States -- Drug use -- Juvenile literature; Drugs -- United States -- Physiological effects -- Juvenile literature; Drug abuse; Drugs -- Physiological effects; Drug abuse -- United States -- Juvenile literature